A Key for Identification of Deltocephaline Genera (Hemiptera: Cicadellidae: Deltocephalinae) Associated with Vegetable Ecosystem in Sri Lanka. - Gnaneswaran, R.; Hemachandra, K.S.; Wijayagunasekara, H.N.P.; Ahangama, D. (Tropical Agricultural Research, 2010)
ABSTRACT. Members of the subfamily Deltocephalinae include many vector species transmitting pathogens among economically important crops. Species of ten genera belonging to seven tribes namely, Exitianus Ball, Nephotettix Matsumura, Deltocephalus Burmeister, Hecalus Stål, Balclutha Kirkaldy, Cicadulina China, Hishimonus Ishihara, Orosius Distant, Changwhania Kwon and Doratulina Melichar were detected in a survey carried out during 2007-2008 in Mid Country associated with the vegetable ecosystems of Sri Lanka. An illustrated dichotomous key based on the morphology and genitalia characters is presented here for easy identification of field collected leafhoppers at generic level.